Extracorporeal shockwave lithotripsy in children: results of treatment in cases of large renal stones - O. A. Shaldenko; I. V. Kliuka; V. V. Sizonov; E. E. Gorishniaya; V. M. Orlov (Вестник урологии, 2019)
Background. The incidence of kidney stone disease (KSD) in children varies from 1% to 5%. Pediatric surgery of KSD employs methods similar to surgical technologies used for adults: extracorporeal shockwave lithotripsy (ESWL), ureterolithotripsy (ULT), retrograde intrarenal surgery (RIRS), percutaneous nephrolithotomy (PCNL), open and laparoscopic lithotomy. ESWL remains the method of choice for urolithiasis management in children; however, the number of publications describing application of minimally invasive procedures (PCNL, RIRS) for large stones in children is increasing. The said existing tendency determines the need for a comparative study in order to reveal the efficiency and safety of ESWL and PCNL/RIRS as treatment methods for large stones in children.Objectives. The study results of the ESWL use in the treatment of children with stones greater than 2 cm.Materials and methods. During the period from 2013 through 2018, ESWL was performed for 146 patients (70 (47.9%) boys and 76 (52.5%) girls) to treat 170 stones. Age of the patients: 6 months to 17 years (mean age: 73 months). Stones were found on the left side in 96 (61.1%) patients, on the right side — in 58 (38.8%) cases, bilaterally — in 16 (9.41%) children. Large stones exceeding 2 cm were diagnosed in 16 patients (8 (50%) boys and 8 (50%) girls). Urolithiasis was revealed on the right side in 3 (18.7%) patients, on the left side — in 11 (68.7%) cases, bilaterally — in 2 (12.5%) children. All patients were subdivided into 2 subgroups: Subgroup I — 6 (37.5%, 7 kidneys) patients with staghorn urolithiasis, Subgroup II — 10 (62.5%, 11 kidneys) patients with non-staghorn stones. Postoperative complications were evaluated in accordance with the Clavien-Dindo classification.Results. In Subgroup I, complete elimination of C-1 stones in one patient took two ESWL sessions (16.67%). Three (50%) children needed 3 ESWL sessions. One (16.67%) child underwent 4 fragmentations. One (16.67%) patient with bilateral C-2 stones had 2 ESWL on the right side, 2 ESWL of the left-side calculus, and 1 ESWL session of stone fragments in distal ureter with prior insertion of ureteral catheter. In Subgroup II, a single ESWL session was sufficient to eliminate a calculus completely in 3 cases (30%). 2 patients (20%) had to undergo two ESWL sessions. 3 patients (30%) needed three ESWL sessions. Four ESWL sessions were carried out for one child (10%). One patient with bilateral stones underwent 2 sessions on the left side, 3 sessions on the right side, the child also had an ESWL to correct the steinstrasse condition in the lower third segment of the left ureter. Grade IIIb postoperative complications according to the Clavien-Dindo classification were observed in 1 (14.9%) patient of Subgroup I and in one (9.09%) patient of Subgroup II. No lithogenesis recurrences were registered.Conclusions. In cases of children suffering from concrements larger than 2 centimetres, ESWL is a safe and efficient procedure even without prior urine derivation resulting in lower incidence of complications compared with other minimally invasive KSD treatment technologies.